2013
DOI: 10.12720/ijoee.1.4.268-273
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of Time Diversity Rain Fade Mitigation Technique for V-band Space-Earth Link Operating in Tropical Climate

Abstract: Satellite communication systems are moving towards greater capacity. Millimeter wave frequency offers a large bandwidth allocation, requires small antenna size and should not experience congested spectrum environment. Nonetheless, rain posses a grave threat to such satellite communication links especially in tropical region where the hydrometeors can severely affect the signal. Rain is the factor that typically limits the implementation or use of higher frequencies for satellite communications in this region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Its efficacy is based on the experimental evidence that rain attenuation decorrelates after few minutes at large fades, and after few tens of minutes at small fades, so that, by transmitting twice (or more times) the same signal with a suitable fixed time delay of the order of several minutes, the receiver can select the best signal and reduce link outage. This description suits the analysis that propagation experts conducted in the past and known, in the theory of diversity systems, as selection diversity. Only recently linear combining techniques have been applied to time diversity system …”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Its efficacy is based on the experimental evidence that rain attenuation decorrelates after few minutes at large fades, and after few tens of minutes at small fades, so that, by transmitting twice (or more times) the same signal with a suitable fixed time delay of the order of several minutes, the receiver can select the best signal and reduce link outage. This description suits the analysis that propagation experts conducted in the past and known, in the theory of diversity systems, as selection diversity. Only recently linear combining techniques have been applied to time diversity system …”
Section: Introductionmentioning
confidence: 91%
“…First proposed by Fukuchi, time diversity is a long‐studied fade countermeasure to rain attenuation, applicable to satellite communication services that can tolerate long time delay (minutes), such as television and audio broadcasting, data transfer from geostationary satellites . Time diversity can be seen as an evolution of the less‐demanding Automatic Repeat Request (ARQ) techniques, because direct and delayed signals are continuously transmitted with a suitable time delay, while in the classic ARQ techniques, the signal is retransmitted in the same channel 2 or more times until it is correctly received.…”
Section: Introductionmentioning
confidence: 99%
“…In [11], it has been demonstrated that rain attenuation via earth-to-satellite link is closely proportional to rain intensity, which attenuation variation occurs throughout the propagation route as a result of rain variation. Previously synthetic storm technique (SST) technique was used [12], [13], [14] to predict rain attenuation time series from measured rain rate time series with and without time delays. However, when compared to measured gain, the technique consistently tends to overestimate gain.…”
Section: Introductionmentioning
confidence: 99%